Новий погляд на громадянське суспільство: реалії і перспективи - Волкова, О.М. (Альманах права, 2012)
У статті досліджуються питання формування сучасного громадянського суспільства, зокрема його сутності, співвідношення із державою, місця особи у взаємодії громадянського суспільства і держави. В статье исследуются вопросы формирования современного гражданского общества, в частности его сущности, соотношение с государством, места личности во взаимодействии гражданского общества и государства. Speaking about the responsibility of the state to the person you want to focus on the responsibility of each to himself. The state can not provide all citizens a high standard of living. Each person must maketheir own effort for their welfare. Civil society is the form for the implementation of initiative, self-manifestation and active social lifeof every person. In our view, this aspect is extremely importantactivities of NGOs. The activity of NGOs is different from the state of the principles of itsoperation. If the activity in the public sector is based on bureaucratic mechanisms, the named organizations operate on the basis of voluntariness, freedom of creativity and self-realization of their members. They are a system of non-profit community organizations that perform some part of social work in society, as well as a forum for the expression of different interests. The existence of a developed civil society focused on people and operates primarily through it. However, this does not mean that other elements of civil society are left aside. Remember that all forms of society made up of individua ls and through their will and consciousness really involved in his life, including in political activities. Civil society is the sphere of private interests of private institutions that are capable of self organization and work closely with each otherand with the state. The state is not opposed to civil society, andcreates favorable conditions for its normal functioning anddevelopment. In this interaction provides a guarantee of resolving legal conflicts arising civilized way, the prevention of socialills and promote the harmonious development of society.